2016
DOI: 10.22178/pos.14-5
|View full text |Cite
|
Sign up to set email alerts
|

Sustaining Small Scale Farming: Evidence of Poverty and income Disparity among Rural Farming Households in South-South Region of Nigeria

Abstract: The incidence of poverty is evidenced among rural farm households in developing societies. As a result of persistence poverty among rural farm households, there is sudden upsurge in agricultural livelihood diversification and rural-urban migration resulting in high rate of urban unemployment. To help generate suitable policy variables to help tackle this rampaging issue in the South-south region of Nigeria, this study specifically analyzes poverty and income inequality as well as identified determinants of pov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 13 publications
3
4
0
Order By: Relevance
“…The study reveals it a ratio 3:1 in terms of access to credit. This agrees with the findings of Akpan et. al., (2013).…”
Section: Resultssupporting
confidence: 94%
“…The study reveals it a ratio 3:1 in terms of access to credit. This agrees with the findings of Akpan et. al., (2013).…”
Section: Resultssupporting
confidence: 94%
“…Hence, those adult family members can engage in off-farm employment to support their family. This finding is consistent with the findings of Vinefall (2015), Akpan et al (2016); Gecho (2016), and Irohibe and Agwu (2014). However, it is inconsistent with the researcher's expectation and money other similar researchers finding.…”
Section: Socio-demographic Factorssupporting
confidence: 93%
“…The educational distribution of respondents indicated that most (85%) had formal education, with the majority (47.33%) having secondary education. It is expected that the high literacy level will facilitate their usage of ICT as their source of information (Akpan, 2016). Omoregie and Igbinosa (2015) also reported that the literate households are most likely to use ICT as their source of obtaining productive information in the farm business.…”
Section: Resultsmentioning
confidence: 99%